Pengembangan Profesionalisasi Guru Untuk Meningkatkan Mutu Pendidikan di Pesantren Darul Quran Tembung - Uswatun Hasanah; Rama Satya Tanjung; Marsyeli Marsyeli; Tasya Widyana; Fachri Habib; Azwar Alamsyahdana (Peneliti.net, 2022)
The purpose of this study was to determine the level of professional competence of teachers and the work of developing teacher competence to improve the quality of education in Darul Quran Tembung pesantren. The teacher is a decisive source and bearer of an important role in every teaching and learning activity, without a teacher teaching and learning will not run well. As a professional, teachers must acquire experience, skills and knowledge in teacher education, in addition to acquiring the scientific content in which they participate. But in reality, educators who do not have full qualifications to carry out their duties, often act as teachers and educators. Until now there are still many teachers who have not carried out their duties as expected due to various obstacles. One of the prevention factors are: The ability of the trainer who does not support the implementation of the task, the ignorance of the trainer himself, the desire and willingness to try to improve his skills. Therefore, teachers must develop, expand, update and deepen their knowledge and skills from time to time. One of the things that need or be prepared to carry out teacher competency development is of course the creation of a creative and innovative work environment so that the goals of educational institutions can be fulfilled properly. One of the efforts to develop teacher skills involves teachers participating in education and training programs both inside and outside the school.